The Constitution of Cádiz - Grimaldi, Angelo (2026)
lthough the Constitution of Cadiz has failed to eliminate the plurality of jurisdictions stemming from the old regime and, at the same time, brought out pre-existing intermediate bodies, which overlapped the abstract concept of "nation", the Spanish text of 1812 qualified Spain as a liberal state. The pre-existing social structures and institutions, which formally attributed a "Spanish guise" to the Constitution, would not have told, in constitutional practice, a different story than the French one, where the decisive and formalseparation of powers slid towards a parliamentary regime in which the Assembly (...)